2003
DOI: 10.1142/s0218127403006765
|View full text |Cite
|
Sign up to set email alerts
|

Finding Cycles in Synchronous Boolean Networks With Applications to Biochemical Systems

Abstract: This paper is an analytical study of Boolean networks. The motivation is our desire to understand the large, complicated and interconnected pathways which comprise intracellular biochemical signal transduction networks. The simplest possible conceptual model that mimics signal transduction with sigmoidal kinetics is the n-node Boolean network each of whose elements or nodes has the value 0 (off) or 1 (on) at any given time T = 0, 1, 2, …. A Boolean network has 2nstates all of which are either on periodic cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 25 publications
1
112
1
Order By: Relevance
“…All experiments can be performed on an Intel Core TM CPU 4300 1.80 GHz with 2 GB memory on an Ubuntu 9.04 Linux server. The top 4 Boolean networks were generated from 5 organisms, including Arabidopsis thaliana (Chaos et al, 2006), budding yeast (Li et al, 2004), Drosophila melanogaster (Albert and Othmer, 2003), T-helper cell (Mendoza and Xenarios, 2006), and protein (Gonze and Goldbeter, 2001;Heidel et al, 2003). In addition to these 5 classical benchmarks, we provide the 2 other randomly generated Boolean networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All experiments can be performed on an Intel Core TM CPU 4300 1.80 GHz with 2 GB memory on an Ubuntu 9.04 Linux server. The top 4 Boolean networks were generated from 5 organisms, including Arabidopsis thaliana (Chaos et al, 2006), budding yeast (Li et al, 2004), Drosophila melanogaster (Albert and Othmer, 2003), T-helper cell (Mendoza and Xenarios, 2006), and protein (Gonze and Goldbeter, 2001;Heidel et al, 2003). In addition to these 5 classical benchmarks, we provide the 2 other randomly generated Boolean networks.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies (Glass and Kaufmann, 1973;Heidel et al, 2003), one condition of sigmoidal kinetics systems was chosen from a complicated environment, which is shown using the following differential equations:…”
Section: A Biological Regulatory Network Examplementioning
confidence: 99%
See 1 more Smart Citation
“…We use two realistic biochemical system examples from previous reports (Robert, 1986;Heidel et al, 2003) to analyze the conditions of the SCAs. To begin, we use a simple affine system (line terms and constant terms) (Milligan and Wilson, 1993;Heidel et al, 2003) as an example.…”
Section: Three Classes Of Scasmentioning
confidence: 99%
“…Recently, Heidel (Heidel et al, 2003) and Farrow (Farrow et al, 2004) found the SCAs in synchronous Boolean networks. Zhao (Zhao, 2005) also proved the computing SCAs' methods in synchronous Boolean networks to be a nondeterministic polynomial time (NP) complete problem.…”
Section: Introductionmentioning
confidence: 99%